PERTANGGUNGJAWABAN PIDANA MAJIKAN YANG MELAKUKAN KEKERASAN DALAM RUMAH TANGGA TERHADAP PEMBANTU RUMAH TANGGA DITINJAU DARI UNDANG-UNDANG NOMOR 23 TAHUN 2004 TENTANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA - Denny Irawan (CALYPTRA, 2014)
Law of the Republic of Indonesia number 23 of year 2004 regarding Elimination of Violence in Household has proposed to protect victims from loss caused violence in household, besides that Law number 23 of year 2004 has proposed to restore the rights of victims are lost caused violence in household. Becaused grade of public ability which relatively low considers violence in household is private interest, so situation like this doesn’t give problem solving, so that violence in household are always going on. The consequences, every violation in household which cause harm to the victim, it should be asked responsibility from perpetrator.